Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1101/gr.247049.118
|View full text |Cite
|
Sign up to set email alerts
|

Replication timing networks reveal a link between transcription regulatory circuits and replication timing control

Abstract: DNA replication occurs in a defined temporal order known as the replication timing (RT) program and is regulated during development, coordinated with 3D genome organization and transcriptional activity. However, transcription and RT are not sufficiently coordinated to predict each other, suggesting an indirect relationship. Here, we exploit genome-wide RT profiles from 15 human cell types and intermediate differentiation stages derived from human embryonic stem cells to construct different types of RT regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 74 publications
(110 reference statements)
1
15
0
Order By: Relevance
“…If this explanation were correct, then fkh1Δ FKH2 cells should show no defect in ARS1529.5 activity because, in the complete absence of Fkh1,Fkh2 should now be able to bind the 5' FKH site. Consistent with this explanation, fkh1∆ cells replicated ARS1529 5.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…If this explanation were correct, then fkh1Δ FKH2 cells should show no defect in ARS1529.5 activity because, in the complete absence of Fkh1,Fkh2 should now be able to bind the 5' FKH site. Consistent with this explanation, fkh1∆ cells replicated ARS1529 5.…”
supporting
confidence: 65%
“…These data provided in vivo evidence that the Fkh1-FHA domain promoted ARS1529.5 activity by binding to the ARS1529. 5 5' FKH site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of these data sets revealed that the developmental lineage of each cell type could be recapitulated on the basis of its replication timing. ENCODE replication timing data have also been used to build background mutation models to study the somatic mutation process 38 and to construct novel, cell type-specific regulatory networks 39 .…”
Section: Expanding Human and Mouse Encodementioning
confidence: 99%
“…The local and global state of chromatin is dynamically altered through a combination of induced forces, torques, and chemical alterations which both operate on, and bridge, the respective length and timescales of cellular function (see Box 1). These effects provide a scaffold for epigenetic memory and a channel for information transmission that must work collectively for the emergence of spatial and temporal fidelity of crucial cellular functions such as replication and transcription (Rivera-Mulia et al, 2019). Gaps remain in our understanding of how transcription and transcriptional regulation impact structures to enable the emergence of new transcriptional states.…”
mentioning
confidence: 99%